Ovid Heroides 11, 13, and 14 : a commentary - Reeson, James. (Mnemosyne, Supplements, 2001)
The volume provides a full literary and textual commentary on three of the verse epistles ( Heroides ) by the Roman poet Ovid (43 BC. - AD. 17): the letter of Canace to her brother-lover Macareus; of Laodamia to the war-hero Protesilaus; and of Hypermestra to Lynceus, the cousin whose life she recently spared. These three poems, together with the letters of Medea (recently the subject of a commentary in the same series) and Sappho, formed the last of Ovid's three books of heroine letters. The introduction discusses Ovid's innovative use both of his sources and of the epistolary form. A text with selective apparatus is provided for each of the three poems, and the detailed commentary is fully indexed.